2010
DOI: 10.1016/j.jacc.2010.03.065
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Schistosomiasis-Associated Pulmonary Arterial Hypertension

Abstract: Sch-PAH has a more benign clinical course than IPAH despite a lack of demonstrable acute vasoreactivity at hemodynamic evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 32 publications
4
57
2
10
Order By: Relevance
“…This study suggests that the etiology of pulmonary hypertension may be closely associated to portal hypertension, a physiopathogeny that shows no significant pulmonary vasoreactivity 8,3 , which is in disagreement with other studies that indicate many similarities between these etiologies, with SPAH being recently reclassified from group IV to group I 17,[27][28][29] . The findings in the analysis are consistent with the fact that patients with SPAH are vasoreactive, but at a value below those recorded for idiopathic PAH, which is around 20% 30 .…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…This study suggests that the etiology of pulmonary hypertension may be closely associated to portal hypertension, a physiopathogeny that shows no significant pulmonary vasoreactivity 8,3 , which is in disagreement with other studies that indicate many similarities between these etiologies, with SPAH being recently reclassified from group IV to group I 17,[27][28][29] . The findings in the analysis are consistent with the fact that patients with SPAH are vasoreactive, but at a value below those recorded for idiopathic PAH, which is around 20% 30 .…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, there was no association with mean pulmonary artery pressure. Of the 84 patients with SPAH, it was observed that 3.5% of them showed criterion for a positive vasoreactivity test with nitric oxide, below the value found for the idiopathic form (10% -20%) 30,35,36 and different from that found by Fernandes et al 8 , in which of 54 schistosomiasis patients, there were no vasoreactive cases. This finding consists in new data that would show that the pulmonary vasoreactivity test is useful in the assessment of severity in patients with schistosomiasis.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…These multiple possible pathways may somehow explain the better clinical course of Sch-PAH. When compared to IPAH, Sch-PAH patients present with a better haemodynamic profile at diagnosis and better prognosis; nonetheless, they still have a 3-yr mortality rate of ,15% [28]. Since schistosomiasis is a highly prevalent disease worldwide and given the non-negligible mortality rate, the reclassification of Sch-PAH in group 1 based on pathological and haemodynamic studies may warrant trials with specific treatments for this highly prevalent condition.…”
Section: Fourth World Symposium On Phmentioning
confidence: 99%